1979
DOI: 10.1080/15287397909529750
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of human liver cancer: Controlled prospective study in liver cirrhosis

Abstract: The incidence of primary liver cell carcinoma was investigated in a prospective study over 6 yr and 5 mo in 403 clinically unselected patients derived from a homogeneous population by means of serial determination of alpha 1-fetoprotein (AFP) by radioimmunoassay. The diagnosis of liver cirrhosis was proved in 90% by laparoscopy and/or histology and/or autopsy. The incidence of primary liver cell carcinoma in liver cirrhosis in the clinically studied patients was 4.47%, significantly lower than in the autopsy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Nevertheless, in most cirrhosis of other etiology (Lehmann and Wegener, 1979; of the developed countries of Europe and North America, Obata et al, 1980;Musca et al, 1983), and that HBV may where the Prevalence of HBs*g carriers is very low but tocause HCC without intervention of cirrhosis (Prince et al, bacco viewed as mutually compatible and fairly consistent in the may act in ways reminiscent of "complete" carcinogenesis (Pitot, 1982); by "initiating" the carcinogenic process through Drogari for her technical assistance.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, in most cirrhosis of other etiology (Lehmann and Wegener, 1979; of the developed countries of Europe and North America, Obata et al, 1980;Musca et al, 1983), and that HBV may where the Prevalence of HBs*g carriers is very low but tocause HCC without intervention of cirrhosis (Prince et al, bacco viewed as mutually compatible and fairly consistent in the may act in ways reminiscent of "complete" carcinogenesis (Pitot, 1982); by "initiating" the carcinogenic process through Drogari for her technical assistance.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that a considerable number of patients with acute and chronic hepatitis and cirrhosis without malignancy might also have slight but significant elevation of serum AFP. 16,17 Frequent rises in adult serum level of AFP are seen in patients with hepatitis and cirrhosis. Positive rates (>10 or 20 ng/ml without detectable differences in the results) reported are 31-52% for acute hepatitis, 15-58% for chronic hepatitis, and 11-47% for cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HCC had the highest incidence and was the third leading cause of cancer death in Korean [2]. Chronic infection with hepatitis B virus, hepatitis C virus, alcohol consumption, and cirrhosis of the liver were recognized as risk factors for primary HCC [3][4][5]. In particular, previous studies had shown that a large proportion of HCC patients in Korea are positive for the hepatitis B virus/hepatitis C viruses, and had suggested that hepatitis B virus and hepatitis C virus infection seemed to play an important role in hepatocarcinogenesis in Korea [6].…”
Section: Introductionmentioning
confidence: 99%